2019
DOI: 10.3390/nu11020322
|View full text |Cite
|
Sign up to set email alerts
|

Association between Sleep Disturbances and Liver Status in Obese Subjects with Nonalcoholic Fatty Liver Disease: A Comparison with Healthy Controls

Abstract: The relevance of sleep patterns in the onset or evolution of nonalcoholic fatty liver disease (NAFLD) is still poorly understood. Our aim was to investigate the association between sleep characteristics and hepatic status indicators in obese people with NAFLD compared to normal weight non-NAFLD controls. Ninety-four overweight or obese patients with NAFLD and 40 non-NAFLD normal weight controls assessed by abdominal ultrasonography were enrolled. Hepatic status evaluation considered liver stiffness determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 70 publications
4
33
0
Order By: Relevance
“…23 Epidemiological studies revealed the association between sleep duration and NAFLD, of which the results, nevertheless, did not reach a consensus. [22][23][24][25] A meta-analysis found an increased risk of NAFLD among individuals with short sleep duration. 22 A study from China revealed the correlation between short sleep duration and an increased risk of prevalent NAFLD among middle-aged and elderly Chinese populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Epidemiological studies revealed the association between sleep duration and NAFLD, of which the results, nevertheless, did not reach a consensus. [22][23][24][25] A meta-analysis found an increased risk of NAFLD among individuals with short sleep duration. 22 A study from China revealed the correlation between short sleep duration and an increased risk of prevalent NAFLD among middle-aged and elderly Chinese populations.…”
Section: Discussionmentioning
confidence: 99%
“…Spanish researchers discovered that sleep disruption might contribute to the pathogenesis of NAFLD, and the alteration of the liver, in turn, might influence sleep patterns. 24 However, Kim et al provided evidence supporting the relationship between longer sleep duration and incidence of NAFLD. 25 Consistent with most of the previous studies, the present study uncovered that hepatic steatosis was attenuated in individuals with longer sleep duration.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, we know that T2DM, obesity, hypertension, and dyslipidemia as the MetS components are the main risk factors for NAFLD. On the other hand, NAFLD development is also influenced by multiple features, such as demographic, genetic, and environmental determinants (23). Therefore, the investigation of the possible influence of other putative factors is becoming in interest of clinicians who manage NAFLD patients.…”
Section: Discussionmentioning
confidence: 99%
“… 25 Sleep disturbance or low sleep quality was also related to increased liver stiffness in patients with NAFLD, which was consistent with our findings, whereas optimal sleep (defined as sleep duration ⩾7 h and ⩽9 h/day) was found to be protective in reducing insulin resistance and liver stiffness. 8 , 26 …”
Section: Discussionmentioning
confidence: 99%
“… 7 , 8 Sleep disruption contributes to the pathogenesis of hepatic steatosis, and short sleep duration is positively associated with liver stiffness. 8 Furthermore, a study reported that insufficient sleep had negative effects on metabolic disorders including diabetes mellitus (DM), obesity, insulin resistance, and metabolic syndrome. 7 However, the relation between sleeping disorder and progression of MAFLD remains unknown.…”
Section: Introductionmentioning
confidence: 99%